MODERN INFORMATION TECHNOLOGIES IN THE STUDY OF THE COURSE «FUNDAMENTALS OF CHEMICAL TECHNOLOGY» - Pylypchuk , Liudmyla; Volkova , Svitlana; Popovych , Tetiana; Reshnova , Svitlana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article deals with the different ways of using new information technologies in the study of Basics of chemical technology.